Out-of-hospital critical case time intervals occuring in the Greater Johannesburg Metropolitan area, Gauteng, as recorded in a paramedic clinical learning database - Van Nugteren, Benjamin Simon (My University, 2015)
Background. Out-of-hospital time intervals are often used to assess Emergency Medical Service (EMS) system performance. In addition, these time intervals are linked to patient outcome in certain time-dependent pathologies such as stroke, out-of-hospital cardiac arrest (OHCA) and myocardial infarction. There are a number of variables that are thought to influence these time intervals such as the number of interventions performed and the transport distance to hospital. Objective. This Johannesburg-based study assessed out-of-hospital critical case time intervals as recorded in a paramedic student clinical learning database. Methods. This retrospective study analysed 19742 cases that were attended to by paramedic students and their clinical supervisors. Of the total number of cases, 1360 critical cases were deemed to meet inclusion criteria in the Greater Johannesburg Metropolitan (GJM) area over the eight-year period under review. Results. Eight hundred and fifty six “trauma” cases and 504 “medical” cases were analysed. The mean response time interval was 10.67 minutes (95% CI:10.48;10.86). Of the critical cases assessed, the mean on-scene time interval was 26.69 minutes (95% CI:26.23;27.15). Generally, critical cases in Johannesburg had longer total incident time intervals (53.53 minutes 95% CI:52.90;54.15) when compared to international data. Conclusions. This study found that when compared to international trends, patients who are critically-ill locally experience similar response time intervals when compared to certain data. On-scene time intervals are comparatively extended. In addition, it was also found that in increase in the number of on-scene interventions led to an increase in on-scene time intervals.